Biodegradable nanoparticles surface modification techniques with cIBR peptide targeting to LFA-1 expressing leukemic cells - Phongpradist R. (American Society of Mechanical Engineers(ASME), 2015)
The lymphocyte function associated antigen-1 (LFA-1) is evaluated for a targeting carrier in leukemia. The cIBR peptide was utilized as the targeting moiety for the drug carrier in direct targeting to LFA-1 expressing cancer cells. This study aims to evaluate the effects of the cIBR peptide conjugation on the specific targeting delivery to the leukemic cell line. Poly (D, L lactide-co-glycolide) (PLGA) nanoparticles were conjugated to the cIBR peptide by three different approaches (coupling, head, and tail) in order to evaluate the nanoparticles' characters, targetability, uptake, drug releasing, and cytotoxicity of each approach. The prepared PLGA nanoparticles were spherical lin shape with a size range of 200-450 nm. The targetability and uptake of three types of cIBR-conjugated nanoparticles (cIBR-NPs) were evidenced and quantified by flow cytometry. The coupling approach presented the highest targetability, uptake, drug releasing, and cytotoxicity followed by the head and tail approaches, respectively. The peptide conjugation method onto the nanoparticles surface was proven to be a key factor for the nanoparticles' physicochemical characteristicss and their efficient delivery. Copyright © 2013 by ASME.